Development of a Web-Based Student Admission System with Cloud Storage for Permanent Registration at Darel Azhar Modern Islamic Boarding School - Dwi Fitria Alfiani; Najwa Masayu Azzahra; Ariyas Pratama; Sutriyono Sutriyono (Journal Majelis Paspama, 2026)
Pondok Pesantren Modern Darel Azhar is currently facing a serious challenge in the form of an unstable registration platform, which frequently changes links every academic year owing to third-party dependencies. The primary impact of this condition is the permanent loss of applicant student (santri) data from previous periods due to the absence of an adequate internal storage system. This study aims to build an independent online student admission information system (PPDB Online) utilizing cloud storage infrastructure to ensure data sustainability and information access stability. The system was developed using the Laravel framework following the SDLC Waterfall model, which encompasses requirement analysis through observation, interviews, and literature reviews. The supporting infrastructure is entirely cloud-based, utilizing Vercel for hosting, TiDB Cloud as the centralized database, and Cloudinary for centralized digital document storage. System testing was conducted using Black-box Testing to ensure feature functionality, and User Acceptance Testing (UAT) to validate that the system meets user requirements and is ready for implementation. The implementation results indicate that this PPDB Online system successfully integrates data into a single centralized database. Consequently, the Islamic boarding school management can securely manage student information from various academic years without the risk of data loss caused by changing platforms. Thus, this system provides full independence for Pondok Pesantren Modern Darel Azhar in managing its information assets while enhancing administrative service professionalism in the digital era.